Too scared to go sick? The management and the manifestations of workplace attendance in the food retail sector. Issue 5 (3rd October 2016) - Hadjisolomou, Anastasios
Abstract: This article is a response to Taylor et al 's (2010) call for further research regarding workplace attendance. It examines the new politics of absence management in the UK and Cyprus in food retail sector, identifying a dual approach in managing attendance across the two countries. The first approach suggested the penalization of absence, whilst the second focused on the prevention of absence through accommodation. The article argues that 'coercion' is not the sole vehicle to tackle high absence in food retailing rather it suggests the development of other practices to enhance cooperation to regular attendance. The research identifies significant differences regarding the formality of these processes between the two countries, and suggests the generation of a particular attendance culture within the organisations, one that is not merely a culture of fear, as Taylor et al (2010) suggest, but rather a culture that includes accommodation and cooperation.